Multimedia: How to Combine Language and Visuals - Horz, Holger; Schnotz, Wolfgang (Language at Work - Bridging Theory and Practice, 2008)
In the last decade, advanced computer technology has allowed for development of information systems and learning environments that combine language with other forms of human communication in innovative ways. Language in the form of written texts, for example, can be combined not only with static pictures or graphs as in printed material, but also with animation or video.